Hak Ingkar Notaris Pengganti Atas Akta Otentik Yang Dibuatnya - Runisari, Amanda; Tanaya, Putu Edgar (Acta Comitas : Jurnal Hukum Kenotariatan, 2022)
This study aims to determine the form of accountability of the substitute notary who has ended his term of office and the extent of his right of refusal. This research uses normative legal research. The responsibility of the Substitute Notary is related to the obligation to keep the secrecy of his office. This applies even after the end of his term, but does not apply for life due to the expiration of a lawsuit. The right of refusal of the Substitute Notary can occur when he is a witness in a matter and is related to the confidentiality of the department to be kept. The right to refusal does not simply happen when he or she is a witness to something. The right of refusal may be exercised when the Substitute Notary complies with the siding call and submits an application to the judge examining the matter. Only then will the judge decide to reject or grant the application